Peran mahasiswa kuliah kerja mahasiswa (kkm) dalam bidang pendidikan di sdn 2 belung - Mutia, Farah (Maliki Interdisciplinary Journal, 2025)
This article examines the role of students in the Student Work Courses (KKM) program at SDN 2 Belung, which aims to improve the quality of education at the primary school level. KKM is an implementation of the Tri Dharma of Higher Education which emphasizes community service. Through a qualitative approach, this study explores various learning methods applied by students, including game-based learning and individualized approaches. The results showed that KKM students succeeded in improving students' literacy skills, with an average increase of 30% after the program was implemented. In addition, students also played a role in empowering teachers and raising community awareness of the importance of education. Despite challenges such as time constraints and the need for better collaboration between all parties, the KKM program is expected to continue and become a model for education development in remote areas.